Transcranial Doppler for Monitoring in the Neurocritical Care Unit - Chaaban, Toufic (2022)
Transcranial sonography is an important component of multimodal monitoring armamentaria in the neurocritical care unit and has multiple clinical applications. Common indications of transcranial sonography include vasospasm monitoring, assessment of cerebral autoregulation, emboli detection, intracranial pressure estimation, target cerebral perfusion pressure estimation and assessment of cerebral circulatory arrest. In addition, the transcranial color coded duplex provides the opportunity to visualize intracranial structures and may be useful in guiding clinical management. Transcranial Doppler (TCD) provides indirect measure of cerebral hemodynamic parameters over a short duration of monitoring and hence, in the current clinical context, daily trends are often more helpful in guiding clinical decisions rather than a specific value at any given time point. Widespread utilization of TCD is limited due to lack of adequate technical and clinical expertise as well as safety directives promoting short duration of monitoring. The advent of automated robotic TCD monitoring devices allow for prolonged automated monitoring of bilateral middle cerebral arteries and has the potential to be useful in guiding goal directed therapy in acute brain injury patients.